Grain tracking at the high energy materials science beamline of the Petra III synchrotron radiation source - King, A; Schell, N; Martins, R; Beckmann, F; Ruhnau, H; Kiehn, R; Marrow, J; Ludwig, W; Schreyer, A (2010)
Grain tracking is a term used to describe experiments that investigate polycrystalline materials in terms of the crystallites or grains from which they are composed, non-destructively and in three dimensions. The new German high brilliance synchrotron radiation source, Petra III, will become available to users in 2010 [1]. The GKSS research centre will operate two beamlines, including the high energy materials science beamline (HEMS) [2]. HEMS will feature an instrument dedicated to grain tracking, able to support a range of experiments of this kind. This paper describes the design and specification of this instrument, and gives examples of the types of experiments that will be possible. © (2010) Trans Tech Publications.